DEVELOPMENT OF STUDENT ACTIVITY SHEET WITH CONTEXTUAL APPROACH ON LINEAR EQUATION SYSTEM MATERIAL OF TWO VARIABLES FOR CLASS VIII - Gendis Ayuwandari; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Some students regard mathematics as a subject matter. Independence, concentration, liveliness, and student self-confidence are still low. The use of existing teaching materials less facilitate students in the process of learning mathematics. This study aims to develop and test Student Worksheet's feasibility (LKS) with a contextual approach on the linear equation system material of two variables for class VIII in Junior High School (SMP). Â This research method uses Research and Development (R & D), covering the stage of preparation, implementation, testing, and revision. The data analysis technique used is the questionnaire instrument analysis. Research subjects are material experts, media experts, and students of grade VIII in SMP. Â The result of the research and development of LKS shows that the material expert's assessment obtained 96,6 score with a very good criterion, from media expert 75,6 with good criterion. Moreover, the result of student response to LKS is good, with a scoring average of 47,75. The result shows that LKS, with a contextual approach on the linear equation system material of two variables for class VIII in SMP, is feasible to be used as learning material in the learning process.